Crystal defects and optical emissions of pulse electrodeposited ZnO. (10th October 2020) - Manzano, Cristina V.; Serrano, Aida; Muñoz-Noval, Álvaro; Fernandez, José F.; Martín-González, Marisol
Abstract: ZnO has been widely studied in the last decades as an n-type semiconductor due to its wide application range, for example, in optoelectronics, solar cells, light-emitting diodes, thermoelectrics, amongst others. The material efficiency for certain applications is highly dependent on the presenting film morphology. Electrodeposition is well-known as a technique with precise control over the structural and morphological properties of the obtained materials. When the structural and morphological properties are tuned, it is possible to find a wide variety of defects in the ZnO structure. In this study, ZnO films were grown using pulsed electrodeposition with variation of the reduction potential. The crystal order, structural defects and optical emissions of the films have been analyzed by X-Ray Diffraction (XRD), X-ray Absorption Near-Edge Structure (XANES), Extended X-ray Absorption Fine Structure (EXAFS) and Photoluminescence (PL). ZnO film grown at less negative reduction potential presents a stronger texture along [0001] by XRD, higher crystalline order, and more zinc vacancies by XANES and EXAFS. The films obtained at less negative potential present less OH − trapped in the ZnO structure and a relatively higher level of defects O i 0, O Z n 0, O i − / 2 − and O Z n 0 / − than those grown at higher reduction potentials by PL. This will be related to the fact that at less negative potentials there is less concentration of OH − at the film surface than at more negative potentials. The combination of X-ray absorption spectroscopy and photoluminescence reveals the complicated nature of the atomic defect in electrodeposited ZnO films. Allowing to evidence the preferential presence of atomic defect as a function of the reduction potential. In this work, we have also compared those defects with reference compounds such as a Zn foil and ZnO polycrystalline powder. Graphical abstract: Image 1